The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.18632/oncotarget.1918
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 antagonists synergize broadly and robustly with compounds targeting fundamental oncogenic signaling pathways

Abstract: While MDM2 inhibitors hold great promise as cancer therapeutics, drug resistance will likely limit their efficacy as single agents. To identify drug combinations that might circumvent resistance, we screened for agents that could synergize with MDM2 inhibition in the suppression of cell viability. We observed broad and robust synergy when combining MDM2 antagonists with either MEK or PI3K inhibitors. Synergy was not limited to cell lines harboring MAPK or PI3K pathway mutations, nor did it depend on which node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 47 publications
5
43
0
Order By: Relevance
“…This intriguing pattern implies that restoring p53 function and blocking the MAPK pathway at the same time could be more beneficial to SKCM patients than interfering with either pathway alone. Studies have shown increased apoptosis and inhibition of melanoma growth by combining a BRAF inhibitor and p53 reactivation (Lu et al, 2013; Saiki et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…This intriguing pattern implies that restoring p53 function and blocking the MAPK pathway at the same time could be more beneficial to SKCM patients than interfering with either pathway alone. Studies have shown increased apoptosis and inhibition of melanoma growth by combining a BRAF inhibitor and p53 reactivation (Lu et al, 2013; Saiki et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…To measure combination effects in excess of Loewe additivity, Horizon has devised a scalar measure to characterize the strength of synergistic interaction termed the Synergy Score [13,14]. The Synergy Score equation integrates the experimentally-observed activity volume at each point in the matrix in excess of a model surface numerically derived from the activity of the component agents using the Loewe model for additivity.…”
Section: Analysis Of Combination Screening Resultsmentioning
confidence: 99%
“…Detailed methods on the combination assay were reported in [14]. Combinations were analyzed using Synergy Score and Loewe Volume Score, as described in [15,16] using Horizon's proprietary Chalice TM Analyzer software.…”
Section: Methodsmentioning
confidence: 99%
“…IC 50 values were calculated using a 4-parameter logistic model in GeneData Screener (Genedata AG). Growth inhibition (GI) was calculated on a 200% scale as described previously (23).…”
Section: Tumor Cell Line Viability Screeningmentioning
confidence: 99%